2003
DOI: 10.1002/ajh.10331
|View full text |Cite
|
Sign up to set email alerts
|

Complete recovery from refractory immune thrombocytopenic purpura in three patients treated with etanercept

Abstract: Management of patients with immune thrombocytopenic purpura (ITP) who have persistent, severe, and symptomatic thrombocytopenia following splenectomy is difficult and empirical. No single agent or regimen provides long-term success for most patients, and for most treatments it is difficult to assess whether benefits outweigh risks. We report three consecutive patients with critical chronic refractory ITP, who responded promptly and completely following treatment with etanercept, an inhibitor of tumor necrosis … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0
1

Year Published

2003
2003
2011
2011

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(19 citation statements)
references
References 21 publications
0
18
0
1
Order By: Relevance
“…Stinco, Piccirillo, and Patrone 9 described a patient receiving etanercept therapy who experienced mild thrombocytopenia that resolved spontaneously without the suspension of the drug, and later confirmed by re-exposure to the same agent with a similar platelet count evolution. Paradoxically, other reports describe the successful use of etanercept 23,24 and infliximab 25 for the treatment of refractory immune thrombocytopenic purpura.…”
Section: Discussionmentioning
confidence: 95%
“…Stinco, Piccirillo, and Patrone 9 described a patient receiving etanercept therapy who experienced mild thrombocytopenia that resolved spontaneously without the suspension of the drug, and later confirmed by re-exposure to the same agent with a similar platelet count evolution. Paradoxically, other reports describe the successful use of etanercept 23,24 and infliximab 25 for the treatment of refractory immune thrombocytopenic purpura.…”
Section: Discussionmentioning
confidence: 95%
“…Although studies evaluating TNF-α in the context of cITP are scarce, the use of a recombinant TNF-α receptor to neutralize TNF-α ameliorates the disease. 21 In agreement with previous results, 3,7 we observed that cITP patients have an upregulation of the Th1 lineage characterized by no detectable serum IL-4 (P<0.001, Figure 1) and increased serum median levels of IL-2 (17.3-fold increase), IL-12p70 (34.8-fold increase) and IFN-γ (1.6-fold increase) (P<0.001 for all, Figure 1), with a concomitant increased percentage of CD4+/IFN-γ+ cells (16.3±11.5 and 5.9±2.29 in patients and controls, respectively, P=0.04) (Figure 2A and B). We also observed that the serum level of IL-2 was correlated with IFN-γ (r=0.42, P<0.001).…”
Section: Resultsmentioning
confidence: 99%
“…Other agents that have been reported in the treatment of ITP are anti-CD154/CD40 [105,106], anti-Fcg RIII [107], soluble TNF-a receptor [108] and anti-IL-2 receptor [109]. These studies have failed to provide sufficient positive results to stimulate further studies.…”
Section: Other Treatment Optionsmentioning
confidence: 90%